A Qualitative Case Study: Women's Experiences and Challenges at Farmers Markets in India - Laxmi Prasanna Kandi; Emmanuel Chisom Okolo; Kim E Dooley (Journal of International Agricultural and Extension Education, 2025)
This study examines the current experiences of women farmers in the Godavarikhani Farmers Market, Peddapalli district, Telangana, India, guided by two research questions: (1) What are the current experiences of women participating in farmers’ markets in the region? and (2) How do these experiences compare to those documented in prior research on women’s participation in Indian farmers’ markets? A qualitative case study design was employed, with semi-structured interviews of twelve women vendors analyzed thematically within Social Capital Theory (SCT). Five themes emerged: economic and market dynamics, community and relationships, motivations and goals, constraints and challenges, and adoption strategies and solutions. The findings show that women’s participation is driven by economic necessity, social support, and cultural continuity. Bonding and bridging capital were evident in trusted customer relations, peer collaboration, and collective problem-solving. However, linking capital was minimum with limiting access to institutional resources. Comparative analysis underscores region-specific and nationwide barriers, calling for gender-responsive infrastructure and inclusive policy reform.
Keywords: Farmer’s market; women farmers; qualitative; Telangana; India; challenges